When Brianna met Bruno ([Beirut] home applied training, 2021)
When Brianna Met Bruno - Explore the importance of social relationships, behaviour and community life. The story have a universal appeal and are accompanied by bright illustrations. The books are a must to enhance the social development of growing children, thus helping them to lead a happier life
English Stories
Keywords: English stories